Isolation and Analysis of various Anthocyanins from the Corolla of Different Varieties of Lantana by TLC Method - MS, Sheeja (International Journal of Pharmaceutical & Biological Archive, 2015)
Isolation and Analysis of various Anthocyanins from the Corolla of Different Varieties of Lantana by TLC Method